Dialog Kehidupan dan Penjanaan Modal Insan Malaysia-Indonesia. - Suraya Sintang; Khadijah Mohd Khambali @ Hambali; Nor Adina Abdul Kadir (2011)
Malaysia-Indonesia share common characteristic in diverse society. However, both are dffir in term of ruling system whereby Malaysian constitution recognise Islam as a Federal religion and simultaneously practice religious freedom for non-Muslim. Conversely, the Republic of Indonesia practice religious freedom without any recognition of certain religion. The dffirence in religious ruling system do not bring them apart to enjoy harmony in diversity. This proof to be the fact in daily life interaction of people from different religious background. This kind of amicable interaction is simply loruwn as Dialogue of life. The study shows that the dialogue of l{e is a mechanism for building competent human capital to live harmoniously with the others. This article aims to discuss various initiatives conducted by Muslims in Malaysia and Indonesia in the activities of dialogue of life at the grassroots level. The participants of the Muslims not only come from the NGOs, but also from the individual experience both in formal and informal interaction. The study proves that the daily life interaction or dialogue of ltfe capable in generating open-minded and accomodative human capital to share living together tffith people in any dffirent situations.